The design fluency test: a reliable and valid instrument for the assessment of game intelligence? - Finkenzeller, T.; Krenn, B.; Würth, S.; Amesberger, G. (German Journal of Exercise and Sport Research, 2021)
The design fluency test (DFT) has been reported to predict successful sports performance of soccer players and has therefore been in the spotlight of sport psychology research. There is, however, a lack of research regarding the psychometric properties of the DFT in elite sports. Thus, the aim of this research was to provide findings of test-retest reliability, practice effects and the diagnostic power of the DFT. Multiple studies of youth and adult elite athletes, as well as nonathlete students, were conducted in applied settings. Test-retest relationship demonstrated poor to acceptable short-term and long-term correlations. Furthermore, significant changes between test and retest were obtained in some variables that differed among samples. The differential value of the DFT was corroborated by significant differences between adolescent students and adolescent elite soccer players. Regarding the prospective value, significant partial correlation coefficients were found between DFT scores and volleyball performance in adult elite players. Although our research partially confirmed previous findings on the differential and prospective power of the DFT, the findings on test-retest reliability indicate that the DFT cannot be recommended for application in sports. The psychometric properties—in particular the findings on test-retest reliability—of the DFT have to be improved before research can be carried out on the application for the selection of team sport athletes and for the prediction of future success in team sports. Further research is needed to develop a scientific instrument for the assessment of game intelligence.